WANITA ASIA DALAM IMAJINASI DIGITAL: KAJIAN LITERATUR ATAS ORIENTALISME - Iman Zanatul Haeri (Jurnal Kajian Wilayah, 2016)
Globalization is marked with the spread of Western culture technology products. One of the Western cultural products that are very influential was Hollywood movies. Fictitious narratives produced the some imaginative ideas that apply also on social media communicative as dating site, video porn sites, until advertising. The awareness of imaginative west of geopolitics outside himself or Other revealed by Edward Said in Orientalism. Said that initially examine the practice of West imaginative through Literature opens up the possibility of resumption of studies on other media with the idea that the West has distortion of the knowledge of the East, one considers that the exotic East. Exotic ideas still present in western digital imagination when respect women Asia as the representation of the women of the east. Some Hollywood movies, dating site, video porn sites until the advertisements still presents stereotypes Asian women foreign, mysterious, strange and sensual display. Asian women trapped in exotic role in the Digital imagination space. They exoticiziation and exoticted themselves before the digital public. Globalisation and the development of communications technology in digital imagination proved does not stop the stereotypes against Asian women that they exotic. Thus through digital imagination and the will of the global capitalism, representation Asian women shown, celebrated, promoted and taken advantage of it.Keywords: digital imagination, women Asia, post-Orientalism, exoticAbstrakGlobalisasi ditandai dengan tersebarnya produk teknologi budaya Barat. Salah satu produk budaya Barat yang sangat berpengaruh adalah film Hollywood. Narasi fiktif tersebut menghasilkan beberapa gagasan imajinatif yang berlaku juga pada media sosial komunikatif seperti situs kencan, video porno, hingga iklan. Kesadaran imajinatif barat terhadap geopolitik di luar dirinya atau other diungkap oleh Edward Said dalam Orientalisme. Said yang pada awalnya mengkaji praktik imajinatif Barat melalui Sastra membuka peluang terbukanya kajian pada media lainnya dengan gagasan bahwa Barat memiliki distorsi pengetahuan tentang Timur, salah satunya menganggap bahwa Timur Eksotis. Gagasan eksotis tetap hadir dalam imajinasi digital Barat ketika memandang Wanita Asia sebagai representasi wanita timur. Beberapa film Hollywood, situs kencan, video porno hingga iklan masih menghadirkan stereotip Wanita Asia yang asing, misterius, aneh dan sensual. Wanita Asia terjebak pada peran eksotisnya dalam ruang imajinasi digital tersebut. Mereka dieksotiskan dan mengeksotiskan diri di hadapan publik digital. Globalisasi dan perkembangan teknologi komunikasi dalam imajinasi digital terbukti tidak menghentikan stereotip terhadap wanita asia bahwa mereka eksotis. Justru melalui imajinasi digital dan kehendak kapitalisme global, representasi wanita asia dipertontonkan, dirayakan, dipromosikan dan diambil keuntungan darinya.Kata kunci: imajinasi digital, wanita Asia, pasca-Orientalisme, eksotis